Odpowiedź :
Odpowiedź:
A) x/3 + 1 = 5/6 + x/2 /·6
2x + 6 = 5 + 3x
2x - 3x = 5 - 6
-x = -1 /:(-1)
x = 1
B) 2x - 3 / 4 = 1/2 + x /·4
2x -3 = 2 + 4x
2x - 4x = 2 + 3
-2x = 5. /:(-2)
x = -2,5
C) x + 2 / 9 + x - 1 / 3 = x - 1 /3 = 1. /·3
3(x + 2) + x - 1 = 3
4x + 6 - 1 = 3
4x = 3 - 6 + 1
4x = -2. /: 4
x = -0,5
D) 2x + 3 / 5 = 2 - x / 3 + x. /·15
3( 2x + 3) = 5( 2 - x) + 15x
6x + 9 = 10 - 5x + 15x
6x + 5x - 15x = 10 - 9
-4x = 1. /:(-4)
x = -0,25
Odpowiedź:
a)
[tex]\frac{x}{3} +1 = \frac{5}{6}+\frac{x}{2}[/tex] |*6
2x + 6 = 5 + 3x
2x - 3x = 5 - 6
-x = -1 |*(-1)
x = 1
b)
[tex]\frac{2x-3}{4}=\frac{1}{2}+x[/tex] |*4
2x - 3 = 2 + 4x
2x - 4x = 2 + 3
-2x = 5 |:(-2)
x = -2,5
c)
[tex]\frac{x+2}{9}+\frac{x-1}{3}=1[/tex] |*9
x + 2 + 3x - 3 = 1
4x -1 = 1 |+1
4x = 2 |:4
x = 0,5
d)
[tex]\frac{2x+3}{5}=\frac{2-x}{3}+x[/tex] |*15
6x + 9 = 10 - 5x + 15x
6x + 9 = 10 + 10x
6x - 10x = 10 - 9
-4x = 1 \:(-4)
x = -1/4
Szczegółowe wyjaśnienie: